2014
DOI: 10.1007/s10461-014-0892-y
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Investigation of Syndemic Conditions Among Young Gay, Bisexual, and Other MSM: The P18 Cohort Study

Abstract: The persistence of disparities in STI/HIV risk among a new generation of emerging adult gay, bisexual, and other men who have sex with men (YMSM) warrant holistic frameworks and new methodologies for investigating the behaviors related to STI/HIV in this group. In order to better understand the continued existence of these disparities in STI/HIV risk among YMSM, the present study evaluated the presence and persistence of syndemic conditions among YMSM by examining the co-occurrence of alcohol and drug use, unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 42 publications
2
60
0
Order By: Relevance
“…In addition, alcohol use, cigarette smoking, stimulants/recreational drug use, and depressive symptoms over time served to increase marijuana use within nearly all marijuana trajectory groups. This finding is consistent with previous studies that found substantial overlap between several types of drug use and other psychosocial health problems [5456]. Accordingly, any prevention approaches to mitigate these behaviors should not focus on one of these behaviors or conditions but must consider these co-occurring conditions holistically.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, alcohol use, cigarette smoking, stimulants/recreational drug use, and depressive symptoms over time served to increase marijuana use within nearly all marijuana trajectory groups. This finding is consistent with previous studies that found substantial overlap between several types of drug use and other psychosocial health problems [5456]. Accordingly, any prevention approaches to mitigate these behaviors should not focus on one of these behaviors or conditions but must consider these co-occurring conditions holistically.…”
Section: Discussionsupporting
confidence: 90%
“…This finding indicates that heterosexual men have a greater item mean, or expected item value when the factor item value is equal to zero, for substance use disorder, anxiety, and depression compared to MSM. Our study extends upon findings that syndemics undermine health and persist across the lifetime of heterosexual men, as well as MSM (73). It is furthermore critical to approach men’s (both heterosexual men and MSM) health holistically by addressing the socio-structural inequities they face that may drive their health behavior and exacerbate their syndemic risk (74).…”
Section: Discussionsupporting
confidence: 80%
“…However, results from the mediation analysis are similar to findings from a few longitudinal cohort studies. 34,35 Third, participants’ responses were subject to recall and social desirability biases, although the mode of survey administration might have mitigated these biases.…”
Section: Discussionmentioning
confidence: 99%